Alcohol and Sexual Assault - Abbey, Antonia (Alcohol Res Health, 2001)
Conservative estimates of sexual assault prevalence suggest that 25 percent of American women have experienced sexual assault, including rape. Approximately one-half of those cases involve alcohol consumption by the perpetrator, victim, or both. Alcohol contributes to sexual assault through multiple pathways, often exacerbating existing risk factors. Beliefs about alcohol’s effects on sexual and aggressive behavior, stereotypes about drinking women, and alcohol’s effects on cognitive and motor skills contribute to alcohol-involved sexual assault. Despite advances in researchers’ understanding of the relationships between alcohol consumption and sexual assault, many questions still need to be addressed in future studies.